2022
DOI: 10.3389/fmed.2022.900809
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT Pathway—The Potential Key Mechanisms of Traditional Chinese Medicine for Stroke

Abstract: Stroke is associated with a high disability and fatality rate, and adversely affects the quality of life of patients and their families. Traditional Chinese Medicine (TCM) has been used effectively in the treatment of stroke for more than 2000 years in China and surrounding countries and regions, and over the years, this field has gleaned extensive clinical treatment experience. The Phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) pathway is important for regulation of cell migration, proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…In addition to DHT, it has been confirmed that Tan I could also promote nuclear Nrf2 protein to increase the expression of related enzymes to combat oxidative stress by the Akt/Nrf2 pathway upregulation [ 41 ]. The classical pathway, phosphatidylinositol-3 kinase (PI3K)/Akt, is essential to regulate various biological processes such as oxidative stress and cellular apoptosis [ 42 , 43 ]. Tan IIA was reported to activate the PI3K/Akt pathway, followed by the upregulation of its downstream mammalian target of rapamycin (mTOR) and endothelial nitric oxide synthase (eNOS) to prevent cellular oxidative stress and apoptosis [ 44 ].…”
Section: Pharmacological Activities Of Tanshinones On Cvdsmentioning
confidence: 99%
“…In addition to DHT, it has been confirmed that Tan I could also promote nuclear Nrf2 protein to increase the expression of related enzymes to combat oxidative stress by the Akt/Nrf2 pathway upregulation [ 41 ]. The classical pathway, phosphatidylinositol-3 kinase (PI3K)/Akt, is essential to regulate various biological processes such as oxidative stress and cellular apoptosis [ 42 , 43 ]. Tan IIA was reported to activate the PI3K/Akt pathway, followed by the upregulation of its downstream mammalian target of rapamycin (mTOR) and endothelial nitric oxide synthase (eNOS) to prevent cellular oxidative stress and apoptosis [ 44 ].…”
Section: Pharmacological Activities Of Tanshinones On Cvdsmentioning
confidence: 99%
“…Inflammation is a hallmark of stroke pathology, and the cytokines is related with infarct evolution (Lambertsen et al, 2012). Akt-related pathways is associated with cell migration, proliferation, apoptosis, oxidative stress, etc., during stroke (Gu et al, 2022). VEGFs participated in the process of cerebral edema, neuroprotection, angiogenesis, etc., in ischemic stroke rats (Greenberg and Jin, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] The repair of various organs in the human body usually proceeds through the PI3K/Akt pathway, especially in the central nervous system. [31] After being phosphorylated by upstream signals, the PI3K/Akt pathway can stimulate downstream proteins to induce a cascade response that is involved in neuroprotection by inhibiting apoptosis, alleviating inflammation and oxidative stress, stimulating angiogenesis, improving cerebral circulation, and many other biological processes (Fig. 9).…”
Section: Results Of Go and Kegg Enrichment Analysismentioning
confidence: 99%